Identification of Mobile Phone Usage's Shifting Among Students - Sutisna, Deni; Widodo, Arif; Anar, Ashar Pajarungi; Indraswati, Dyah; Nursaptini, Nursaptini (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2020)
This study aims to identify the use of mobile phones in SMAN 1 Pangalengan. The survey was conducted on 100 students. Data collection using a questionnaire. Data analysis uses quantitative descriptive methods. The results showed students tend to utilize social media such as Facebook, Instagram, and WhatsApp. Other uses for browsing, gaming, and entrepreneurship. Survey results show that 92% of students use WhatsApp to communicate and 82% of students use mobile phones to access social media. This shows the pattern of mobile phone use has shifted among students although basically, it does not change the main function.